2017
DOI: 10.1159/000479236
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Intractable Tremor-Dominant Parkinson Disease: A Retrospective Analysis

Abstract: Objective: The purpose of this study was to retrospectively analyze the outcomes of stereotactic radiosurgery for patients suffering from medically refractory Parkinson disease (PD) tremor. Methods: We retrospectively studied the outcomes of 33 patients who were treated with gamma knife thalamotomy (GKT) over a 19-year period. Twelve patients were ≥80 years. A median dose of 140 Gy (range, 130-150 Gy) was delivered to the nucleus ventralis intermedius through a single 4-mm isocenter. We used the Fahn-Tolosa-Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
3
0
4
Order By: Relevance
“…Однако возрастание частоты побочных эффектов и осложнений лекарственной терапии привело к возобновлению интереса к хирургическому лечению в 90-х годах XX в. Это произошло во многом благодаря работам L. Laitinen и соавт., показавших, что, в отличие от терапии препаратами леводопы, стереотаксические вмешательства способны устранять многие симптомы этого заболевания без значительных побочных эффектов [14]. В настоящее время накоплен большой опыт радиохирургических операций, которые являются разновидностью стереотаксической деструкции [1,5,[15][16][17][18][19].…”
Section: Russian Journal Of Neurosurgeryunclassified
See 2 more Smart Citations
“…Однако возрастание частоты побочных эффектов и осложнений лекарственной терапии привело к возобновлению интереса к хирургическому лечению в 90-х годах XX в. Это произошло во многом благодаря работам L. Laitinen и соавт., показавших, что, в отличие от терапии препаратами леводопы, стереотаксические вмешательства способны устранять многие симптомы этого заболевания без значительных побочных эффектов [14]. В настоящее время накоплен большой опыт радиохирургических операций, которые являются разновидностью стереотаксической деструкции [1,5,[15][16][17][18][19].…”
Section: Russian Journal Of Neurosurgeryunclassified
“…Уменьшение выраженности тремора достигается у 70-90 % пациентов [11,13,[15][16][17]19]. Положительный эффект радиохирургии в подавляющем большинстве случаев возникает отсроченно и в среднем проявляется через 5 мес (от 3 до 12 мес), хотя имеются сообщения о прекращении тремора как через 1 нед после лечения [19], так и более чем через 1 год [11]. В нашем исследовании среднее время наступления положительного эффекта -4 мес, что соответствует данным большинства авторов.…”
Section: рис 1 фотография пациента (а) и магнитно-резонансная томография (б) при фиксации стереотаксической рамы рама расположена таким оunclassified
See 1 more Smart Citation
“…Bilateral thalamotomy remains insufficiently researched and lacks publication in contemporary literature ( 8 ). One publication has focused on GK treatment for a patient with refractory Parkinson's disease (PD) tremor, with tremor assessment measured by the Fahn-Tolosa-Marin Rating Scale (FTRS) ( 9 ). Results showed that 70.0% of examined patients experienced full tremor relief, while an optimistic 93.9% had a significant reduction of tremor ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…One publication has focused on GK treatment for a patient with refractory Parkinson's disease (PD) tremor, with tremor assessment measured by the Fahn-Tolosa-Marin Rating Scale (FTRS) ( 9 ). Results showed that 70.0% of examined patients experienced full tremor relief, while an optimistic 93.9% had a significant reduction of tremor ( 9 ). Although GK has great potential in the treatment of symptoms associated with various syndromes, there remains the standing issue of a 3-6 month delay of tumor suppression.…”
Section: Introductionmentioning
confidence: 99%